2020
DOI: 10.3389/fcell.2020.00485
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Rechallenge Decreases Metastatic Potential but Increases Cell Viability and Clonogenicity in a Tamoxifen-Mediated Cytotoxicity-Resistant Subline of Human Breast MCF7 Cancer Cells

Abstract: Background: Drug resistance is frequently found in estrogen receptor-positive (ER +) breast cancer patients during and after prolonged tamoxifen treatment. Although tamoxifen rechallenge has been proposed for treating recurrent breast tumors, the clinical benefit of this treatment is still controversial. The aims of this study are to identify the possible tamoxifen cytotoxicity-resistant subpopulation of MCF7 cells and to determine the effects of tamoxifen rechallenge on these cells. Methods: Western blot anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It has been reported that tamoxifen resistant cells undergo adaptions that leads to various biological changes including loss of epithelial-like structure and acquisition of stem cells properties 20 . Here, morphological changes and E-Cad downregulation along with overexpression of cancer stem cell markers were observed in MCF-7 TamR cells compared to control cells, indicating successful establishment of tamoxifen resistance model.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that tamoxifen resistant cells undergo adaptions that leads to various biological changes including loss of epithelial-like structure and acquisition of stem cells properties 20 . Here, morphological changes and E-Cad downregulation along with overexpression of cancer stem cell markers were observed in MCF-7 TamR cells compared to control cells, indicating successful establishment of tamoxifen resistance model.…”
Section: Discussionmentioning
confidence: 99%